Growth, photosynthetic activity, and potassium and sodium concentration in rice plants under salt stress - doi: 10.4025/actasciagron.v34i3.13687 - Morales, Soledad García; Trejo-Téllez, Libia Iris; Gómez Merino, Fernando Carlos; Caldana, Camila; Espinosa-Victoria, David; Herrera Cabrera, Braulio Edgar (Acta Scientiarum. Agronomy, 2011)
Salt stress affects crop growth and productivity. In this study, we determined the growth, yield of photosystem II (PSII), and K+ and Na+ concentration in root, stem, old leaves, and young leaves of two Mexican varieties of rice, Tres Ríos and Cotaxtla. In addition, the K+/Na+ ratio in stem and root of both varieties was determined. The experiment was conducted in a growth chamber under controlled conditions, under a completely randomized distribution, with a 2 x 2 (Variety x Salinity) factorial arrangement and 12 replications. Plants were grown in a hydroponic solution for 15 days and then some of them were treated with 100 mM NaCl; control plants (without NaCI treatment) were grown in parallel. Salt stress caused 20 and 15% reductions in stem and root length, respectively, in the variety Tres Ríos, while in the variety Cotaxtla no significant differences were observed in these variables compared to the control. Dry matter weight decreased by 24% in the variety Tres Ríos. The quantum yield of PSII decreased by 30% the third day of treatment application, in both varieties. Na+ concentration was significantly (p ≤ 0.05) higher in NaCI-treated plants. In the variety Tres Ríos, the yield of PSII was completely eradicated six days after treatment implementation, while the K+ concentration in stem and older leaves also decreased and the lowest K+/ Na+ ratio in stem was recorded, which could indicate that it is more susceptible to salinity than the variety Cotaxtla.